Échelles et variations des couleurs des champs - Jean-Pierre Husson (VertigO)
This is a personal, sensitive and even poetic reflection. It approaches this subject through a kind of traversal geography, or even ego-geography of nurturing landscapes. Their diversity is renewed by the transience and variations of colors according to technical itineraries. This approach differs from a methodological framework already explored elsewhere. Tones and colors are mainly the result of the farmers' work, and the strategies adopted to apply crop rotations. Colors are above all a reflection of hurried temporalities. They are too often simplified, drawn in large grids. The scale of terroirs, of fine mosaics, has long served as a benchmark for European rural landscapes, but is waning at a time when solid french networks of Trames vertes et bleues (TVB) are being called for. Color is a criterion for assessing agrosystems capable of resilience, adaptation and inventive projections for the future. We note a distortion between, on the one hand, the anxious, even angry, agrarian reality, the imposed constraint of having to feed around 9 billion people and, on the other hand, the desire for local countryside expressed by our fellow citizens.